Answer:
b. x² + 8x + 12 =
1. use the factoring X (see attachment)
2. 6 x 2 = 12; 6 + 2 = 12
3. (x + 6)(x + 2) = 0
4. x = -6, -2
c. x² + 13x + 12 =
1. 12 x 1 = 12; 12 + 1 = 13
2. (x + 12)(x + 1) = 0
3. x = -12, -1
c. x² + x - 12 =
1. 4 · (-3) = -12; 4 - 3 = 1
2. (x +4)(x - 3) = 0
3. x = -4, 3
f. x² + 15x + 36 =
1. 12 x 3 = 36; 12 + 3 = 15
2. (x + 12)(x + 3) = 0
3. x = -12, -3
hope this helps :)
Answer:
A) Yes, 7
Step-by-step explanation:
The given sequence An = {13, 20, 27, 34, ...}
Here the first term Ao = 13 and difference between the successive terms is (d) = 7
That is d = 20 - 13
d = 7
It is an arithmetic sequence. d = 7
Answer: Yes, it is arithmetic sequence and common difference (d) = 7
Thank you.
Answer:
f^-1(x)= -x/5 - 4/5
Step-by-step explanation:
I’m hoping this helps (but hopefully now you can give the brainliest to the person above)
I’m not very familiar with the square roots method but I believe you try and isolate the term that is squared.